Regenerative electromagnetic dampers in high-rise buildings - Schwabauer, Matthew (Kansas State University, 2020)
High-rise buildings constantly sway due to the influence of wind. This movement is especially noticeable for tall and slender buildings because they inherently have smaller stiffness than shorter, less slender buildings and therefore have larger drifts. This issue can be mitigated with the use of a tuned mass damper (TMD) which reduces the wind-induced dynamic response of high-rise buildings. Conventional TMDs have viscous dampers to help dissipate energy of the building motion through heat transfer to the environment. This report proposes a new type of damper that can be used instead of viscous dampers that would convert the dissipated building energy into electricity. The proposed type of damper is called an electromagnetic (EM) damper and uses induced Eddy currents to create the damping effect needed to mitigate building movement. The report reviewed experimental and numerical studies that have been conducted on this novel energy regeneration system. These studies found that in a specific case 27.4% of the total energy stored in building oscillation can be converted to electricity. This report followed a case study, Taipei 101, and calculated that the building stores 108 kW of power during a light breeze. Applying the efficiency found in the aforementioned studies to Taipei 101 provides 30 kW of electricity that could be produced from this regenerative TMD system during light wind conditions. Regenerative TMDs with EM dampers have the potential to produce a significant amount of electricity while maintaining effective movement control for high-rise buildings, but the current cost of these devices is too high to be economically feasible with current technology.
Keywords: Energy regeneration; Tuned mass damper; Wind induced vibration; High rise building; Taipei 101; Structural dampers